Calculus

f(x)=4sinx/1+cosx

find f'(x)

this is what i got and i dunno what i did to get it wrong

(4cos(x)+ 4cosx^2-4sin(x)^2)/cosx62

  1. 👍 0
  2. 👎 0
  3. 👁 102
asked by Justin
  1. looks like a ± error, and your denominator is wrong

    my first line of the derivative was

    (1+cosx)(4cosx) - 4sinx(-sinx))/(1+cosx)^2 using the quotient rule
    expanding :
    (4cosx + 4cos^2x + 4sin^2x)/(1+cosx)^2
    = 4(cosx + 1)/(1+cosx)^2 , remember sin^2x+cos^2 = 1
    = 4/(1+cosx)

    1. 👍 0
    2. 👎 0
    posted by Reiny

Respond to this Question

First Name

Your Response

Similar Questions

  1. Calculus

    If f(x)=4sinx/1+cosx then f'(x)=_____? I think that the derivative of 4sinx would be 4cos and cosx would be sinx but I don't know where to go from there.

    asked by gnozahs on June 5, 2009
  2. calc

    The equation of the tangent line to y=f(x) at a=2 can be written in the form y=mx+b where f(x) =4sinx/4sinx+6cosx i already got 3/2 for m but i cant seem to find out how to get the value of b?

    asked by sonia on May 9, 2008
  3. Trigonometry Check

    Simplify #3: [cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [cosx-(sin90cosx-cos90sinx)sinx]/[cosx-(cos180cosx+sinx180sinx)tanx] = [cosx-((1)cosx-(0)sinx)sinx]/[cosx-((-1)cosx+(0)sinx)tanx] = [cosx-cosxsinx]/[cosx+cosxtanx] =

    asked by Anonymous on February 20, 2012
  4. Pre-Calc

    Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= tanx + secx My work so far: (sinx/cosx + 1/cosx + cosx/cosx)/(sinx/cos x - 1/cosx + cosx/cosx)= tanx + cosx (just working on the left side) ((sinx + 1 -

    asked by Dave on January 2, 2007
  5. Trig........

    I need to prove that the following is true. Thanks (cosx / 1-sinx ) = ( 1+sinx / cosx ) I recall this question causing all kinds of problems when I was still teaching. it requires a little "trick" L.S. =cosx/(1-sinx) multiply top

    asked by abdo on April 18, 2007
  6. Math

    Verify the identity . (cscX-cotX)^2=1-cosX/1+cosX _______ sorry i cant help you (cscX-cotX)=1/sinX - cosX/sinX = (1-cosX)/sinX If you square this you have (1-cosX)^2/(sinX)^2 Now use (sinX)^2 = 1 - (cosX)^2 to get (1-cosX)^2 / 1 -

    asked by Rose on October 9, 2006
  7. Precalculus/Trig

    I can't seem to prove these trig identities and would really appreciate help: 1. cosx + 1/sin^3x = cscx/1 - cosx I changed the 1: cosx/sin^3x + sin^3x/sin^3x = cscx/1-cosx Simplified: cosx + sin^3x/sin^3x = cscx/1-cosx I don't

    asked by Heather on August 15, 2014
  8. Maths

    Solve this equation fo rx in the interval 0

    asked by Edward on April 11, 2007
  9. Math

    How many solutions does the equation cosx + 1/2 = 1 have for 0

    asked by Jake on January 25, 2012
  10. Trigonometry.

    ( tanx/1-cotx )+ (cotx/1-tanx)= (1+secxcscx) Good one! Generally these are done by changing everything to sines and cosines, unless you see some obvious identities. Also generally, it is best to start with the more complicated

    asked by mo on April 18, 2007

More Similar Questions